Tunisia : Fourth Review Under the Extended Fund Facility Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Tunisia's Fourth Review Under the Extended Fund Facility (EFF) Arrangement and Request for Modification of Performance Criteria (PCs). The recovery has proceeded broadly as expected in the Third Review, notwithstanding elevated socio-political tensions and a further increase in oil prices. Growth accelerated to 2.8 percent in the second quarter driven by agriculture and tourism. The authorities met all Quantitative PCs and implemented two out of the three Structural Benchmarks due for the Fourth Review, notably the competitive central bank foreign exchange auctions. The IMF staff supports the authorities' request for completion of the Fourth Review under the EFF arrangement.